2023
DOI: 10.1021/acsomega.3c00236
|View full text |Cite
|
Sign up to set email alerts
|

C3 Functionalization of Indolizines via HFIP-Promoted Friedel–Crafts Reactions with (Hetero)arylglyoxals

Abstract: A highly efficient Friedel–Crafts type hydroxyalkylation at the C3 position of indolizines with (hetero)arylglyoxals has been achieved by the action of hexafluoroisopropanol (HFIP) under mild reaction conditions, leading to direct access to a variety of polyfunctionalized indolizines in excellent yields. Installation of more diverse functional groups at the C3 site of indolizine scaffold was realized via further elaboration of the resulting α-hydroxyketone moiety, allowing for expansion of indolizine chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While Vilsmeier–Haack formylation of 12a delivered 19 in 71% yield, Mannich reaction of 12a with formaldehyde and morpholine gave 20 . Friedel–Crafts-type monoaddition of 12a to phenylglyoxal in the presence of HFIP led to 21 in 81% yield . Compound 12ad underwent Suzuki–Miyaura cross-coupling smoothly to afford 22 .…”
Section: Resultsmentioning
confidence: 99%
“…While Vilsmeier–Haack formylation of 12a delivered 19 in 71% yield, Mannich reaction of 12a with formaldehyde and morpholine gave 20 . Friedel–Crafts-type monoaddition of 12a to phenylglyoxal in the presence of HFIP led to 21 in 81% yield . Compound 12ad underwent Suzuki–Miyaura cross-coupling smoothly to afford 22 .…”
Section: Resultsmentioning
confidence: 99%
“…To validate our hypothesis, the requisite starting material 1 (when LG is OH) was envisioned to be easily prepared via a Friedel–Crafts-type reaction between phenol and arylglyoxal [ 24 ]. Inspired by our recent success in achieving the hexafluoroisopropanol (HFIP)-mediated hydroxyalkylation of indolizine 3 to arylglyoxal to afford 4 ( Scheme 1 b) [ 25 ], we expected that a HFIP-promoted Friedel–Crafts-type reaction between phenol 5 and arylglyoxal would give rise to 7 , which could be converted to benzofuran 8 , having an indole at the C3 position upon exposure to indole and p -toluenesulfonic acid (PTSA) ( Scheme 1 c). The biological investigation of benzofuran–indole hybrid 8 [ 26 ] revealed that this class of compounds exhibit anticancer activity against PC9 and A549 lung cancer cells via the inhibition of phosphorylated EGFR.…”
Section: Introductionmentioning
confidence: 99%